Lower Serum Vitamin D Metabolite Levels in Relation to Circulating Cytokines/Chemokines and Metabolic Hormones in Pregnant Women with Hypertensive Disorders - Adela, Ramu; Borkar, Roshan M.; Mishra, Navneeta; Bhandi, Murali Mohan; Vishwakarma, Gayatri; Varma, B. Aparna; Ragampeta, Srinivas; Banerjee, Sanjay K. (Frontiers in Immunology, 2017)
We aimed to investigate whether lower serum vitamin D metabolites levels were associated with altered cytokine/chemokine and metabolic hormones levels in three different hypertensive disorders in pregnancy. Healthy pregnancy (n=30) and hypertension disorders in pregnancy (n=30) i.e. gestational hypertension, preeclampsia, and eclampsia subjects were enrolled. Vitamin D metabolites were measured by LC-MS/MS method. Circulatory 27 cytokines/chemokines and 10 metabolic hormones were measured. Significantly decreased 25(OH)D and 1,25(OH)2D levels were observed in hypertensive disorders in pregnancy. 25(OH)D levels were significantly lower in preeclampsia and eclampsia while serum 1,25(OH)2D levels were significantly decreased only in eclampsia subjects. Serum 25(OH)D and 1,25(OH)2D levels were negatively correlated with systolic- and diastolic blood pressure, creatinine, uric acid levels. Serum IL-6 and IL-13 decreased and GIP levels were increased in gestational hypertensive subjects. PDGF-BB and IL-8 levels were increased and MIP-1beta levels were decreased in eclampsia subjects. IL-8 and IL-10 increased, and rantes and GIP levels decreased in eclampsia group as compared with gestational hypertension group. Multivariate logistic regression analysis showed that Eotaxin, MCP-1, 25(OH)D, and 1,25(OH)2D were predictors of hypertensive disorders in pregnancy. Our analyses suggest lower Vitamin D metabolites are associated with altered cytokines/chemokines and metabolic hormones in hypertension disorders in pregnancy.